Pengaruh Penggunaan Instagram Terhadap Gaya Ootd Mahasiswa Program Studi Ilmu Komunikasi Universitas Dehasen Bengkulu - Tunnazila, Hikma; SM, Anis Endang; Octaviani, Vethy (Professional: Jurnal Komunikasi dan Administrasi Publik, 2024)
Currently, Instagram is widely used by various groups of people. Instagram makes people easy to access and get the information needed, especially in OOTD style. This study aims to determine the effect of using Instagram on OOTD style in Communication Studies Program Students at Dehasen University Bengkulu. Technology Determination Theory is the theory used in this study, also as an analysis knife to see how technology in the form of Instagram can affect human lifestyle, especially in OOTD style. To determine the effect of Instagram use on OOTD style, researchers used the t test, which shows that the results of the t value of 7.732 and t table of 75 are 1.995. Because the value of t count> t table or 7.732> 1.995, it means that Ha is accepted, it can be said that there is an influence between Instagram usage on OOTD style. This means that the more often you use Instagram, the more people know what OOTD Style is.